The Bible's Encouragement to Be Active Implementing Learning Planning - Dwi Ariefin (KAPATA: Jurnal Teologi dan Pendidikan Kristen, 2021)
Planning is an activity that also determines the success of learning. Planning activities in the practical form of compiling learning tools, such as syllabus, RPS, or RPP, cannot be ignored. The teachers have been trained, directed and even supervised to do so. However, some Christian teachers are not necessarily willing to do it diligently. For those who have not or who have done, need to be strengthened with a stronger encouragement. The Bible is the authoritative Word of God and can be a source of encouragement for every Christian, including Christian teachers. Therefore, it is necessary to find Bible truths that are relevant to planning. Excavated Bible passages, especially those relevant to the topic. After investigation, found truths that are ready to be applied; that the planning is: 1) Needs to be done; 2) It is necessary to ask for God's participation in carrying it out; 3) Need to be implemented properly; 4) the activity is closed with submission to God's will. Christian teachers who value the authority of the Bible will pay attention to and obey God's Word to do well in lesson planning.